Higher-order motion sensitivity in fly visual circuits - Lee, Yu-Jen (National Academy of Sciences, 2012)
In higher-order motion stimuli, the direction of object motion does not follow the direction of luminance change. Such stimuli could be generated by the wing movements of a flying butterfly and further complicated by its motion in and out of shadows. Human subjects readily perceive the direction of higher-order motion, although this stands in stark contrast to prevailing motion vision models. Flies and humans compute motion in similar ways, and because flies behaviorally track bars containing higher-order motion cues, they become an attractive model system for investigating the neurophysiology underlying higher-order motion sensitivity. We here use intracellular electrophysiology of motion-vision–sensitive neurons in the hoverfly lobula plate to quantify responses to stimuli containing higher-order motion. We show that motion sensitivity can be broken down into two separate streams, directionally coding for elementary motion and figure motion, respectively, and that responses to Fourier and theta motion can be predicted from these. The sensitivity is affected both by the stimulus’ time course and by the neuron’s underlying receptive field. Responses to preferred-direction theta motion are sexually dimorphic and particularly robust along the visual midline.